An Examination of the Utility of Shareholder Agremmentin Nigeria: The Imperative to give it a Statutory Leverage - Gabriel, Adenyuma Iji; Suleman, Abdulrasheed Lanre (NIU Journal of Humanities, 2018)
The mode of management of a company and the rights of its shareholders is provided by statute while the internal relationship between the shareholders inter se and between the shareholders and the company as well as its operation, management and corporate governance structure upon, its incorporation, are provided for in its Article of Association. Too often people set up companies with friends and relatives but do not contemplate protecting their interests in the company until it is too late. In practice lawyers, in an attempt to cover myriad interests of shareholders, would populate the Memorandum and Articles of Association with all manner of clauses which in themselves hardly address the core issues requiring shareholder protection. The Articles of Association of the company, most times do not offer a shareholder full protection. The greatest risk an owner of a minority interest in a private company suffers is that he will be shut out of decision making. This clearly discounts the shareholder’s statutory and contractual obligation to the company’s sustainability. This work examines the nature of shareholders’ agreement and its utility having regard to the obvious detached relationship between companies and the greater majority of shareholders in Nigeria. The paper finds a less than formalized approach to shareholder agreement structure in Nigeria and advocates for a legislative action to make it an incorporation document as a component of shareholder protection regime in Nigeria.